A dialogic perspective between the productive structure and the narratives of Argentine television fictions (2011-2020) - Carboni, Ornela Vanina (2022)
This article analyzes how the ownership structure and the alliances between the agents producing serialized fiction for television are linked to the themes and narratives addressed by this type of cultural product. From the political economy of communication and cultural studies, the paper examines the predominant themes in the 100 most watched premiere fictions on open television in Argentina during the decade between 2011 and 2020. It is concluded that there is a wide predominance of universal themes with nonstructural local references, over purely local ones.